The BAHD Gene Family in Cacao (Theobroma cacao, Malvaceae): Genome-Wide Identification and Expression Analysis - Abdullah; Faraji, Sahar; Heidari, Parviz; Poczai, Péter (Frontiers in Ecology and Evolution, 2021)
BAHD enzymes play a critical role in regulating plant metabolites and affecting cell stability. In the present study, BAHD gene family members were recognized in the genome of Theobroma cacao and characterized using available bioinformatics tools. We found 27 nonredundant putative tcBAHD genes in cacao for the first time. Our findings indicate that tcBAHD genes are diverse based on sequence structure, physiochemical properties, and function. In addition, tcBAHDs and BAHDs of G. raimnodii, and C. capsularis were clustered into four main groups. According to phylogenetic analysis, BAHD family genes were probably evolve drastically after divergence. The divergence time of duplication events with purifying selection pressure was predicted to range from 1.82 MYA to 15.50 MYA. Pocket analysis revealed that serine amino acid more present in binding site than other residuals that shows a key role of this amino acid in regulating the activity of tcBAHDs. Furthermore, cis-acting elements related to responsiveness of stress and hormone, especially ABA and MeJA were frequently observed in the promoter region of tcBAHD genes. Besides, RNA-seq analysis illustrated that tcBAHD13 and tcBAHD26 are more involved in response to P. megakarya fungi. In conclusion, it seems that evolutionary processes, such as duplication events, caused a high diversity in the structure and function of tcBAHD genes.